(Using the Swom Strategy and Its Impact on Generating Alternative Ideas among Female Students of the Institute of Fine Arts in the Pottery Sculpture Course) (Journal of the College of Basic Education, 2025)
The study intends to measure the effects of training in Swom strategy. To fulfill the purpose of study, the researcher intended to test the following hypothesis:There is no significant difference (0.05) between the mean of the experimental group pre-and post-cognitive test scores of students.In order to test the hypotheses, the researcher performed the experiment from 2/19/2025 through 4/16/2025. The research body was provided by the students of Institute of Fine Arts. The research subjects were chosen among the students in the Department of Fine Arts - 4th grade - morning students, including 11 female ones. The researcher also utilized two pre- and post-test in the experimental design (one group).The main findings arrived by the researcher; is that Swom strategy has obtained increasing of experimental students' cognitive achievement scores in favor of them after application for a while. Accordingly, the researchers did reach some conclusions but I do not believe enough to demonstrate effectiveness for motivational strategy swom. This is due to the fact that when students performed the experiment themselves, they became more motivated to learn. Thus, the researcher proposes a few recommendations like:Efforts to generate interest around contemporary (modern) teaching and learning methods that could enhance mental development amongst students.2. Prepare training courses by educational institutions for in-service teachers, enabling them to use effective teaching strategies, including (Swom3. Adopting the Swom strategy in teaching pottery sculpture to students in the Department of Art Education, given its proven success with the research sample.4. The Ministry of Higher Education must provide a bright learning environment that aims to develop students' mental abilities.